Random Fiber Grating Characterization Based on OFDR and Transfer Matrix Method - Zichao Zhou; Chen Chen; Ping Lu; Stephen Mihailov; Liang Chen; Xiaoyi Bao (Sensors, 2020)
Random fiber gratings (RFGs) have shown great potential applications in fiber sensing and random fiber lasers. However, a quantitative relationship between the degree of randomness of the RFG and its spectral response has never been analyzed. In this paper, two RFGs with different degrees of randomness are first characterized experimentally by optical frequency domain reflectometry (OFDR). Experimental results show that the high degree of randomness leads to low backscattering strength of the grating and strong strength fluctuations in the spatial domain. The local spectral response of the grating exhibits multiple peaks and a large peak wavelength variation range when its degree of randomness is high. The linewidth of its fine spectrum structures shows scaling behavior with the grating length. In order to find a quantitative relationship between the degree of randomness and spectrum property of RFG, entropy was introduced to describe the degree of randomness induced by period variation of the sub-grating. Simulation results showed that the average reflectivity of the RFG in dB scale decreased linearly with increased sub-grating entropy, when the measured wavelength range was smaller than the peak wavelength variation range of the sub-grating. The peak reflectivity of the RFG was determined by <semantics>κ2LΔP</semantics> (where <semantics>κ</semantics> is the coupling coefficient, <semantics>L</semantics> is the grating length, <semantics>ΔP</semantics> is period variation range of the sub-grating) rather than <semantics>κL</semantics> when <semantics>ΔP</semantics> is larger than 8 nm in the spatial domain. The experimental results agree well with the simulation results, which helps to optimize the RFG manufacturing processes for future applications in random fiber lasers and sensors.